FIRM ETHICALITY, GREEN MARKETING, AND BRAND LOYALTY: MODERATING EFFECTS OF BRAND REPUTATION, ENVIRONMENTAL CONCERN, AND SOCIAL INFLUENCE - Pradana, Mahir; Bryant , De Roger Baggio; Rubiyanti , Nurafni (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study examines the influence of firm ethicality, green marketing, and corporate social responsibility (CSR) on brand loyalty toward Tokopedia, it also explores the moderating roles of brand reputation, environmental concern, and social influence. A survey of 56 Tokopedia users was analyzed using partial least squares structural equation modeling (PLS-SEM). Results show that firm ethicality significantly and positively influenced brand loyalty. In contrast, green marketing and CSR did not show significant effects, nor did any of the hypothesized moderating relationships. Interestingly, social influence, although not proposed as a direct predicator, demonstrated a significant direct effect on brand loyalty, highlighting the roles of normative and informational influence in e-commerce. Assessment of the measurement model confirmed satisfactory construct reliability, convergent validity, and discriminant validity. The structural model exhibited predictive relevance. The findings indicate that corporate ethics and social influence are key factors in fostering loyalty within Indonesia’s digital marketplace.